A classification of congenital uterine anomalies predicting pregnancy outcomes. (23rd May 2014) - Takami, Mio; Aoki, Shigeru; Kurasawa, Kentaro; Okuda, Mika; Takahashi, Tsuneo; Hirahara, Fumiki
Abstract Objective To evaluate pregnancy outcomes in women with uterine anomalies by applying a method for diagnosing and classifying congenital uterine malformations. Design Retrospective study. Setting Tertiary care center. Population Ninety‐four women with uterine anomalies who delivered after 22 gestational weeks. Methods Excluding the 14 women with a history of surgery and seven with one endometrial cavity, 73 women with two endometrial cavities were subdivided into those with two external uterine orifices (2‐OS subgroup) and those with one external uterine orifice (1‐OS subgroup). Main outcome measures Pregnancy outcomes, such as preterm birth, abnormal fetal presentation, cesarean delivery and placental abruption. Results The 2‐OS subgroup comprised women with a didelphic or complete septate uterus who had a significantly higher rate of cesarean delivery (91% vs. 18%, p < 0.001) than the control group (normal uterine morphology; n = 5763). The 1‐OS subgroup comprised women with a bicornuate or incomplete septate uterus who had significantly higher rates of preterm birth (27% vs. 5%, p < 0.001) and placental abruption (14% vs. 0.7%, p < 0.001) than the control group. Conclusions Classification of uterine anomalies by the number of uterine endometrial cavities and external uterine orifices is an easy and reliable means of predicting pregnancy outcomes.